Investigating brain community structure abnormalities in bipolar disorder using path length associated community estimation. Issue 5 (25th June 2013) - GadElkarim, Johnson J.; Ajilore, Olusola; Schonfeld, Dan; Zhan, Liang; Thompson, Paul M.; Feusner, Jamie D.; Kumar, Anand; Altshuler, Lori L.; Leow, Alex D.
Abstract In this article, we present path length associated community estimation (PLACE), a comprehensive framework for studying node‐level community structure. Instead of the well‐known Q modularity metric, PLACE utilizes a novel metric, ΨPL, which measures the difference between intercommunity versus intracommunity path lengths. We compared community structures in human healthy brain networks generated using these two metrics and argued that ΨPL may have theoretical advantages. PLACE consists of the following: (1) extracting community structure using top‐down hierarchical binary trees, where a branch at each bifurcation denotes a collection of nodes that form a community at that level, (2) constructing and assessing mean group community structure, and (3) detecting node‐level changes in community between groups. We applied PLACE and investigated the structural brain networks obtained from a sample of 25 euthymic bipolar I subjects versus 25 gender‐ and age‐matched healthy controls. Results showed community structural differences in posterior default mode network regions, with the bipolar group exhibiting left‐right decoupling. Hum Brain Mapp 35:2253–2264, 2014. © 2013 Wiley Periodicals, Inc.